Hydrodynamic behaviours of fine sediment in retention structure using particle image velocimetry / Masoumeh Moayeri Kashani - Masoumeh, Moayeri Kashani (2016)

(untitled)
Siltation, or sediment pollution, is a cause for water pollution by fine particles of clay or silt. Accumulated fine sediments create murky water with low oxygen levels, potentially leading to aquatic life death. Thus, studying the hydrodynamic behavior of fine sediments is essential. However, the direct evaluation of fine particle suspension and deposition is costly and limiting. The intent of this research is to display a novel, direct outlook of the hydrodynamic behavior of fine sediments in the two-dimensional study of retention structures with different hydraulic features using particle image velocimetry (PIV). To attain this goal, the physical and mechanical properties of fine sediment are investigated extensively by applying rheological methods, laser diffraction particle size analysis (LDPSA) and scanning electron microscopy (SEM). The rheological behavior of six soil samples (fine particles with D < 63 μm) from different regions of Malaysia is explored. A rotational rheometer with a parallel-plate measuring device (two sizes: 25 mm and 50 mm) is used to observe the flow and viscoelastic properties of fine particles. The samples undergo the rheological curve and amplitude sweep test methods to investigate the effect of water content ratio, and texture and structure of particles on the rheological properties. Therefore, the hydrodynamic behavior of a mix of water and fine particles is studied in a specifically designed sediment basin. The fluid is seeded with fluorescent polymer particles of two sizes (20-50 and 1-20 μm). Then the impact of different hydraulic parameters, such as water depth, flow rate, particle diameter, varying inlet distances from the water surface, and outlet placement, on fine particle movement in the middle of the designed basin is observed. Fine particle displacement is identified by recording images with a CCD (charge coupled device) camera and using Nd-YAG laser lighting. The fine sand, clay and silt content affect the stiffness, structural stability and shear behavior of soil. Moreover, the concentration of fine sediment particles in water directly influences the rheological curve. Reduced viscosity of samples with higher water concentrations is iv detected. Consequently, a substantial quantity of fine sediments are distributed within the water body and remain suspended over time. As a result, the sedimentation rate slows down. Apparently, the flow rate modifies the velocity and direction of fine particles, while at the bottom of the basin, approaching the outlet, the re-suspension rate increases at higher flow rates. The same inlet and outlet level reduces fine particle dispersion, while a lower flow rate assists with controlling high siltation. The gravitational force affects the fine particles more at greater depth, thus boosting the settling level more than 50%. Thus, the supreme collecting efficiency is investigated at water surface near 80%. Furthermore, there is a direct correlation between flow rate and particle size, while a higher inlet and outlet hinder the dispersion of fine particles in the water column. Smaller spherical particles have greater influence on fine particle suspension. Therefore, controlling the hydraulic parameters can ultimately reduce the siltation problem.